Prophetic Ethics and the Foundations of Islamic Leadership - Fauziah, Mira (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2025)
This study explores the ethical and theological foundations of leadership as reflected in the prophetic traditions (ḥadīth) of Islam. In light of contemporary challenges—such as moral erosion, authoritarian tendencies, and the neglect of justice in Muslim leadership—this research revisits key ḥadīth to recover the prophetic vision of governance rooted in responsibility, consultation, and public service. Employing a mawḍūʿī (thematic) approach, the study analyzes three core aspects of leadership: the obligation to establish leadership in a community, the method and ethical considerations for selecting a leader, and the moral accountability of those in power. Drawing from authentic ḥadīth collections and classical commentaries, the findings reveal that leadership in Islam is both a religious and rational imperative (farḍ kifāyah) aimed at safeguarding unity, promoting justice, and ensuring communal welfare. The prophetic model redefines leadership as a trust (amānah), where every individual—from political leaders to heads of households—is accountable for those under their care. These insights remain profoundly relevant, offering an ethical framework for leadership that transcends hierarchy and invites a return to compassionate, principled governance.